Variation in susceptibility status to organophosphate insecticide among several geographic populations of Aedes albopictus Skuse in Indonesia - Budi Mulyaningsih, Budi Mulyaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Aedes albopictus skuse is an important vector of dengue fever and dengue hemorrhagic fever in Southeast Asia. Its distribution in Indonesia extends from Sabang (Sumatera) to Merauke (Papua) and is currently expanding. In response to a potential dengue fever outbreak in Indonesia during 2002, the susceptibility of 4 geographic populations of Aedes albopictus Skuse to commonly used mosquito adulticide (malathion) and larvicide (temephos) were assessed.Objective: The aim of this study is to determine the susceptibility status of each Ae. albopictus population to malathion and temephos.Methods: Eggs collected from 4 different geographic area in Indonesia, such as Padang (Sumatera), Yogyakarta (Java), Banjar (Kalimantan) and Timika (Papua) were reared to larvae and adults and were investigated by using bioassay (World Health Organization, 1981). The bioassay data were analyses using Probit analysis, which also corrects for mortality in the controls by Abott formula.Result: The Ae. albopictus mosquito population originate from Yogyakarta shows highest LC50 and LC90 malathion and temephos value, and the Ae. albopictus mosquito population originate from Timika shows lowest LC50 and LC90 malathion and temephos value than other population.Conclusion: There were insecticide susceptibility status difference of Ae. albopictus from diffetent geographic population in Indonesia (Padang, Yogyakarta, Banjar and Timika).Key words: malathion Ã¢â¬â temephos - Ae. albopictus - bioassay - Abott formula.